Encyclopedia of remote sensing - Njoku, Eni G. (Encyclopedia of Earth Sciences Series,, 2014)
Remote sensing has revolutionized the scientific study of the Earth by enabling measurements of more detailed and hitherto unexplored phenomena with spatially-extensive and global perspectives. Various disciplines and industries have benefited from the dramatic discoveries enabled by remote sensing. This volume cuts across these disciplines and describes the basic foundations, principles and state of the art of remote sensing. It covers the development of remote sensing, the theoretical underpinnings, forward modeling, commercial applications, and global and international coordination and policy. This first encyclopaedic reference on remote sensing describes the concepts, techniques, instrumentation, data analysis, interpretation, and applications of remote sensing, both airborne and space-based. Scientists, engineers, academics, and students can quickly access answers to their reference questions and direction for further study.